2020
DOI: 10.3390/ijerph17041364
|View full text |Cite
|
Sign up to set email alerts
|

An Innovative Treatment Approach Using Digital Workflow and CAD-CAM Part 1: The Restoration of Endodontically Treated Molars in Children

Abstract: Stainless steel crowns are the most popular restoration technique for young permanent first molars treated endodontically. However, these restorations are not aesthetically appealing and need to be replaced. Endocrowns constitute a reliable approach for restoring severely damaged molars and premolars. Intraoral scanners (IOSs) are well tolerated by children and are easily and quickly implemented. We present an innovative treatment approach for endodontically treated teeth in children, using a digital workflow … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
10
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 21 publications
1
10
0
2
Order By: Relevance
“…An increasing number of dentists are purchasing and implementing intraoral scanners (IOS) for making optical impressions of oral soft and hard tissues as an alternative to traditional impressions, which are generally poorly tolerated by patients [1][2][3]. The area of application previously consisted mostly of quadrant imaging [4][5][6][7][8]. However, as systems become faster, more accurate, and easier to use [9,10], more clinicians are scanning complete arches and wide-spanning dental restorations [11][12][13].…”
Section: Introductionmentioning
confidence: 99%
“…An increasing number of dentists are purchasing and implementing intraoral scanners (IOS) for making optical impressions of oral soft and hard tissues as an alternative to traditional impressions, which are generally poorly tolerated by patients [1][2][3]. The area of application previously consisted mostly of quadrant imaging [4][5][6][7][8]. However, as systems become faster, more accurate, and easier to use [9,10], more clinicians are scanning complete arches and wide-spanning dental restorations [11][12][13].…”
Section: Introductionmentioning
confidence: 99%
“…The biomechanical properties of fiber posts are more comparable to that of dentine decreasing the risk of accidental root fractures [ 6 ], but building an adequate ferrule can necessitate crown lengthening leading to unfavorable crown to root ratio [ 7 ]. Developments in dental materials [ 8–10 ], computer-aided design/computer-aided manufacturing (CAD/CAM) technologies [ 11 , 12 ] and bonding systems [ 13 , 14 ] improve the application of endocrowns [ 15 , 16 ] to restore the ETT, that prevents the failures of posts [ 17 , 18 ]. Endocrown preparation preserves the dental structure, which has supragingival margins on peripheral enamel tissue enhancing adhesive capacity [ 19 ].…”
Section: Introductionmentioning
confidence: 99%
“…In the literature, it has been reported that a digital impression obtained from intraoral scanners increases patient comfort by preventing the gag reflex 4 . CAD/CAM systems enable the fabrication of more precise dental restorations by eliminating extensive laboratory work and human‐based errors 9,10 . Together with these advantages, CAD/CAM systems offer fast, effective, and comfortable treatment options as an alternative to conventional treatments 5,8,10 …”
Section: Introductionmentioning
confidence: 99%
“…CAD/CAM systems enable the fabrication of more precise dental restorations by eliminating extensive laboratory work and human‐based errors 9,10 . Together with these advantages, CAD/CAM systems offer fast, effective, and comfortable treatment options as an alternative to conventional treatments 5,8,10 …”
Section: Introductionmentioning
confidence: 99%